2019
DOI: 10.1111/wrr.12723
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wound fluid biomarkers to determine healing in adults with venous leg ulcers: A prospective study

Abstract: Clinical practice guidelines recommend using repeated wound surface area measurements to determine if a chronic ulcer is healing. This results in delays in determining the healing status. This study aimed to evaluate whether any of a panel of biomarkers can determine the healing status of chronic venous leg ulcers. Forty-two patients with chronic venous leg ulcers had their wound measured and wound fluid collected at weekly time points for 13 weeks. Wound fluid was analyzed using multiplex enzymelinked immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 34 publications
(53 reference statements)
1
33
0
Order By: Relevance
“…While this is the first study to investigate the proteomic changes within a VLU treated with a placental‐derived product, this is not the first study to investigate changes in wound fluid of healing and non‐healing chronic wounds. Stacey et al also reported a number of differentially expressed growth factors and cytokines in the wound fluid of healing and non‐healing VLUs including Eotaxin, GM‐CSF, ICAM‐1, IL‐6, IL‐16, MCP‐1, MIP‐1a, MMP‐13, PDGF‐BB, and TIMP‐4 37 . Similarly, Edsberg et al conducted a proteomic analysis on the wound fluid of pressure ulcers and identified 20 proteins which were also differentially expressed between chronic and healed wounds including GM‐CSF, I‐309, INF‐γ IL‐11, IL‐12p40, IL‐15, IL‐1a, IL‐1b, IL‐8, TIMP‐1, TIMP‐2 TNF RI, TNF RII, ICAM‐1, IL‐16, MIP‐1d, MMP‐10, MMP‐13, MMP‐3, and Eotaxin‐2 38 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…While this is the first study to investigate the proteomic changes within a VLU treated with a placental‐derived product, this is not the first study to investigate changes in wound fluid of healing and non‐healing chronic wounds. Stacey et al also reported a number of differentially expressed growth factors and cytokines in the wound fluid of healing and non‐healing VLUs including Eotaxin, GM‐CSF, ICAM‐1, IL‐6, IL‐16, MCP‐1, MIP‐1a, MMP‐13, PDGF‐BB, and TIMP‐4 37 . Similarly, Edsberg et al conducted a proteomic analysis on the wound fluid of pressure ulcers and identified 20 proteins which were also differentially expressed between chronic and healed wounds including GM‐CSF, I‐309, INF‐γ IL‐11, IL‐12p40, IL‐15, IL‐1a, IL‐1b, IL‐8, TIMP‐1, TIMP‐2 TNF RI, TNF RII, ICAM‐1, IL‐16, MIP‐1d, MMP‐10, MMP‐13, MMP‐3, and Eotaxin‐2 38 .…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Edsberg et al conducted a proteomic analysis on the wound fluid of pressure ulcers and identified 20 proteins which were also differentially expressed between chronic and healed wounds including GM‐CSF, I‐309, INF‐γ IL‐11, IL‐12p40, IL‐15, IL‐1a, IL‐1b, IL‐8, TIMP‐1, TIMP‐2 TNF RI, TNF RII, ICAM‐1, IL‐16, MIP‐1d, MMP‐10, MMP‐13, MMP‐3, and Eotaxin‐2 38 . In this study, we observed similar trends as seen in other studies with TIMP‐4, IL‐1a, and MMP‐10 37,38 . Prior studies have identified that protease levels within the wound bed of VLUs may be predictive of the outcome of the wound, specifically MMP‐1, 39 MMP‐2, 39,40 MMP‐7, 39 and MMP‐9 33,39‐41 ; however, it should be noted that there is no current consensus that protease activity is an indicator of healing in VLUs 42 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, a multi-omics approach to evaluating putative biomarkers associated with disease involves collecting biopsy samples from patients and transferring these to a laboratory for quantification using specialist techniques; for example, enzyme-linked immunosorbent assays (ELISAs) 5 or liquid chromatography–mass spectrometry (LC–MS). 8 This adds to lengthy analytical procedures as clinical samples have to be prepared in accordance with the assays employed.…”
Section: Introductionmentioning
confidence: 99%